Metals Ions Removal by Polymer Membranes of Different Porosity. (28th May 2013) - Jasiewicz, Katarzyna; Pietrzak, Robert
Abstract : The effect of the amount of pore generating agent (polyvinylpyrrolidone) added to standard polymer membranes containing 18 wt.% of polyethersulfone on the physicochemical properties of the membranes and their capacity for removal of iron and copper ions from the liquid phase was studied. The membranes were obtained by the phase inversion method. The results have shown that the modification of polymer membranes by the use of different amounts of the pore forming agent in their syntheses leads to significant changes in porosity and has beneficial effect on equilibrium water content. The membranes studied were found to show different acid-base surface character, but for all membranes studied, a significant dominance of oxygen groups of acidic character was evidenced. The most effective were the membranes of the lowest content of polyvinylpyrrolidone, while the lowest values of resistance showed the membranes of the highest content of PVP, and so the ones of the greatest porosity.